2023
DOI: 10.3390/su152416551
|View full text |Cite
|
Sign up to set email alerts
|

Biochar Amendment in Vermi-Wetland for Enhancing Nitrification during Excess Sludge Recycling

Ting Bai,
Gratien Twagirayezu,
Zhen Wang
et al.

Abstract: Vermi-wetland is a sustainable technology for recycling excess sludge in small-town areas. Although biochar (BC) amendment into the vermi-wetland could considerably boost the effectiveness of treating sludge, its impact on the nitrogen transformation in vermi-wetland remains unclear. Hence, this study aimed to explore the mechanism and performance of BC amendment into the vermi-wetland for enhancing nitrogen transformation during excess sludge recycling. The semi-aquatic plant Acorus calamus and the earthworm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Typically, the large surface area of biochar promotes an adsorptive activity. Several scanning electron microscopy studies have confirmed that biochar adsorbs contaminants on its surface area (Cederlund et al 2016;Bai et al 2023).…”
Section: Direct Influences Of Biochar On Adsorption and Sorption Of P...mentioning
confidence: 97%
“…Typically, the large surface area of biochar promotes an adsorptive activity. Several scanning electron microscopy studies have confirmed that biochar adsorbs contaminants on its surface area (Cederlund et al 2016;Bai et al 2023).…”
Section: Direct Influences Of Biochar On Adsorption and Sorption Of P...mentioning
confidence: 97%